Hydrothermal vents supporting persistent plumes and microbial chemoautotrophy at Gakkel Ridge (Arctic Ocean) - Wegener, Gunter; Molari, Massimiliano; Purser, Autun; Diehl, Alexander; Albers, Elmar; Walter, Maren; Mertens, Christian; German, Christopher R.; Boetius, Antje (Frontiers in Microbiology, 2024)
Hydrothermal vents emit hot fluids enriched in energy sources for microbial life. Here, we compare the ecological and biogeochemical effects of hydrothermal venting of two recently discovered volcanic seamounts Polaris and Aurora of the Gakkel Ridge in the ice-covered Central Arctic Ocean. At both sites persistent hydrothermal plumes rose up to 800 m into the deep Arctic Ocean. In the two nonbuoyant plumes, rates of microbial carbon fixation were strongly elevated compared to background values of 0.5-1 µmol m -3 day -1 in the Arctic deep water, which suggests increased chemoautotrophy on vent-derived energy sources. In the Polaris plume, free sulfide and up to 360 nM hydrogen enabled microorganisms to fix up to 46 µmol inorganic carbon (IC) m -3 day -1 , and this energy pulse resulted in the strong increase of the relative abundance of SUP05 with in average 25% and Candidatus Sulfurimonas pluma with in average 7% of all bacteria. At Aurora, microorganisms fixed up to 35 µmol IC m -3 day -1 . Here metal sulfides limit the bioavailability of reduced sulfur species, and the putative hydrogen oxidizer Ca. S. pluma constitutes 35% and SUP05 10% of all bacteria. In accordance with this data, transcriptomic analysis showed a high enrichment of hydrogenase-coding transcripts in Aurora, and an enrichment of transcripts coding for sulfur oxidation in Polaris. There was neither evidence for methane consumption nor substantial increase of the abundance of putative methanotrophs or their transcripts in either plume. Together, our results demonstrate the dominance of hydrogen and sulfide as energy sources in Arctic hydrothermal vent plumes.